Magnetic resonance imaging correlation with molecular and epigenetic markers in assessment of breast cancer - Aya S. El-Rawy; Hoda Y. Abdallah; Marwa A. Suliman; Mohamed R. Habba; Azza A. Gad (The Egyptian Journal of Radiology and Nuclear Medicine, 2022)
Abstract Background Breast cancer is a heterogeneous disease with a wide range of clinical behavior, histologic subtypes, therapeutic options, and outcomes. The different biology and histology of breast cancer display different tumor morphology at breast magnetic resonance imaging (MRI). However, few studies have examined the relationship between the MRI morphological, kinetic features and molecular and epigenetic markers in breast cancer assessment. The study aimed to evaluate the correlation between MRI morphological and kinetic features, molecular and an epigenetic marker (linc-ITGB1) in breast cancer cases. A total of 115 women (80 cases and 35 controls) with BIRAD 4 category breast lesions were included. The association between the MRI morphological & kinetic features, apparent diffusion coefficient (ADC) values, and molecular and the epigenetic marker (linc-ITGB1) was evaluated using Mann–Whitney and Chi-square tests. Results The shape (p = 0.009), size of the lesion (p = 0.003), and pattern of enhancement (p ≤ 0.001) were significantly correlated with the molecular markers. Luminal subtypes are more likely to be presented with irregular shaped and non-circumscribed margin masses (97% for luminal A and 94.1% for luminal B). Triple-negative cancers are frequently presented with regular masses, circumscribed margins, and peripheral rim enhancement (50% of TN tumors). HER2-positive cancers are more likely to be multifocal/multicentric and are more associated with non-mass pattern of enhancement as compared to HER2-negative cancers. Perilesional edema was also significantly correlated with HER2-positive lesions (p = 0.009). Although the epigenetic marker linc-ITGB1 was overexpressed by 4.85-folds in breast cancer cases compared to benign controls, we could not find any significant correlation between its expression level and the MRI features or molecular subtypes (p = 0.948). Conclusions MRI features can be a reliable predictor of breast cancer molecular subtypes. The epigenetic marker linc-ITGB1 has a potential role in breast cancer pathogenesis but with no significant correlation with either the MRI features or molecular subtypes of the lesions.